Pain-Induced Impact on Movement: Motor Coordination Variability and Accuracy-Based Skill - Hasan Arieh; Behrouz Abdoli; Alireza Farsi; Abbas Haghparast (Basic and Clinical Neuroscience, 2022)
Introduction: Studies on pain are generally conducted for two purposes: first, to study patients with pain who have physical changes due to nerve and muscle lesions, and second, to regain the appropriate kinematic post-pain pattern. The present study aimed to investigate the effect of pain on the coordination variability pattern and throwing accuracy. Methods: The study participants included 30 people aged 18-25 years who volunteered to participate in the study. Participants practiced and acquired skills in 10 blocks of 15 trials. In the test phase associated with pain, Individuals were randomly divided into three groups: local pain, remote pain, and control. In their respective groups, participants were tested in a 15-block trial, 24 hours, and 1 week after acquisition. Results: The results revealed that pain did not affect the throwing accuracy (P=0.456). Besides, in the phase of acceleration in throwing, movement variability in the pain-related groups in the shoulder and elbow joints (P=0.518), elbow and wrist (P=0.399), and the deceleration and dart drop phase movement variability in the pain-related groups in the shoulder and elbow joints (P=0.622), elbow and wrist (P=0.534). Conclusion: Based on the results, the accuracy and coordination variability in pain-related groups were similar. However, to confirm these results, more research is needed on performing motor functions in the presence of pain.